Asuhan Gizi Klinik pada Pasien Rawat Inap Demam Berdarah Dengue (DBD)+Vomitting+Bronkitis di Rumah Sakit Bhayangkara H.S. Samsoeri Mertojoso Surabaya - Nisrina Abidah; Dominikus Raditya Atmaka (Media Gizi Kesmas, 2023)
Background: DHF patients accompanied by vomiting and bronchitis require proper nutritional care to speed up the healing process. Dengue virus causes inflammation, causing the appearance of metabolic stress which is characterized by an increase in body temperature. The nutritional care provided is the TKTP diet to prevent tissue damage due to infection.   Objectives: Analyze the Standardized Nutritional Care Process carried out on inpatient DHF patients at Bhayangkara H.S. Mertojoso Hospital Surabaya. Methods: Type of observational descriptive study with data collection techniques by interviews and medical record analysis. Results: Patients were given a TKTP diet with energy requirements of 2300 kcal, protein 132 gr, carbohydrates 299 gr, and fat 64 gr. Soft form of food. After monitoring for three days, it was found that there was an increase in excessive intake with the highest intake characterized by a percentage of intake exceeding 110% of daily needs. The highest intake is fat because patients also consume food from outside the hospital. Conclusions: The patient's intake was good but tends to be excessive. This was caused by the consumption of food from outside the hospital. The advice given was to provide education to patients and families to only consume food from the hospital so that intake can be more controlled. After discharge from the hospital, patients must take better care of the hygiene and sanitation of the dormitory room to prevent the breeding of Aedes aegypti mosquitoes and control the intake consumed to maintain endurance and gain an ideal weight.